Failure Of Hearing Acquisition in Mice With Reduced Expression of Connexin 26 Correlates With the Abnormal Phasing of Apoptosis Relative to Autophagy and Defective ATP-Dependent Ca2+ Signaling in Kölliker’s Organ - Sun, Lianhua; Gao, Dekun; Chen, Junmin; Hou, Shule; Li, Yue; Huang, Yuyu; Mammano, Fabio; Chen, Jianyong; Yang, Jun (Frontiers in Cellular Neuroscience, 2022)
Mutations in the GJB2 gene that encodes connexin 26 (Cx26) are the predominant cause of prelingual hereditary deafness, and the most frequently encountered variants cause complete loss of protein function. To investigate how Cx26 deficiency induces deafness, we examined the levels of apoptosis and autophagy in Gjb2loxP/loxP; ROSA26CreER mice injected with tamoxifen on the day of birth. After weaning, these mice exhibited severe hearing impairment and reduced Cx26 expression in the cochlear duct. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) positive cells were observed in apical, middle, and basal turns of Kölliker’s organ at postnatal (P) day 1 (P1), associated with increased expression levels of cleaved caspase 3, but decreased levels of autophagy-related proteins LC3-II, P62, and Beclin1. In Kölliker’s organ cells with decreased Cx26 expression, we also found significantly reduced levels of intracellular ATP and hampered Ca2+ responses evoked by extracellular ATP application. These results offer novel insight into the mechanisms that prevent hearing acquisition in mouse models of non-syndromic hearing impairment due to Cx26 loss of function.